2009
DOI: 10.1084/jem.20082818
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-2 is a Syk-coupled pattern recognition receptor crucial for Th17 responses to fungal infection

Abstract: Innate immune cells detect pathogens via pattern recognition receptors (PRRs), which signal for initiation of immune responses to infection. Studies with Dectin-1, a PRR for fungi, have defined a novel innate signaling pathway involving Syk kinase and the adaptor CARD9, which is critical for inducing Th17 responses to fungal infection. We show that another C-type lectin, Dectin-2, also signals via Syk and CARD9, and contributes to dendritic cell (DC) activation by fungal particles. Unlike Dectin-1, Dectin-2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
297
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(308 citation statements)
references
References 63 publications
9
297
1
1
Order By: Relevance
“…Zymosan, which can activate both Dectin-1 and Dectin-2, increases the transcription and secretion of IL-12p70, IL-23, IL-6, and IL-1␤ by BMDC, which in turn promotes the development of Th1 and Th17 immune responses. Robinson et al found that BMDC from B6 mice required only 1 of the two Dectin receptors in order to make TNF-␣ and IL-10 in response to zymosan (83), implying that the function of the two receptors was redundant if a fungal particle is recognized by both receptors. Mutation of either receptor makes mice more susceptible to systemic Candida albicans infection, though this may depend on the strain of C. albicans used to infect the mice (31,84,85).…”
Section: Discussionmentioning
confidence: 99%
“…Zymosan, which can activate both Dectin-1 and Dectin-2, increases the transcription and secretion of IL-12p70, IL-23, IL-6, and IL-1␤ by BMDC, which in turn promotes the development of Th1 and Th17 immune responses. Robinson et al found that BMDC from B6 mice required only 1 of the two Dectin receptors in order to make TNF-␣ and IL-10 in response to zymosan (83), implying that the function of the two receptors was redundant if a fungal particle is recognized by both receptors. Mutation of either receptor makes mice more susceptible to systemic Candida albicans infection, though this may depend on the strain of C. albicans used to infect the mice (31,84,85).…”
Section: Discussionmentioning
confidence: 99%
“…25 However in contrast to dectin-1 which, during canonical signaling, interacts with Syk directly, dectin-2 induces signaling through Syk indirectly by association with the FcRg chain. 26 Blockade of dectin-2 expressed on DCs has been reported to reduce Th17 responses during systemic infection with C. albicans.…”
mentioning
confidence: 99%
“…However, immune defense mechanisms against Coccidioides infection in the extrapulmonary organs and tissues are poorly understood. MyD88 and Card9 are two cytosolic immune adaptors that transduce signals from IL-1 receptor/Toll-like receptors (TIR/TLRs) and C-type lectin receptors (CLRs), respectively, to bridge innate and adaptive immunity (20,(40)(41)(42)(43)(44)(45). We recently reported that MyD88-and Card9-mediated signaling pathways contribute to the development of vaccine-induced Th17 and Th1 immunity against pulmonary Coccidioides infection (18,19).…”
Section: Discussionmentioning
confidence: 99%